Manipulating the morphology of the nano oxide domain in AuCu–iron oxide dumbbell-like nanocomposites as a tool to modify magnetic properties. Issue 40 (19th June 2018) - Najafishirtari, Sharif; Lak, Aidin; Guglieri, Clara; Marras, Sergio; Brescia, Rosaria; Fiorito, Sergio; Sadrollahi, Elaheh; Litterst, Fred Jochen; Pellegrino, Teresa; Manna, Liberato; Colombo, Massimo
Abstract : We highlighted the effects of oleic acid on the structural and magnetic properties of colloidal nanodumbbells. Abstract : We report the colloidal synthesis of hybrid dumbbell-like nanocrystals (NCs) which feature a plasmonic metal domain (M) attached to a morphologically-tunable magnetic oxide domain (MOx). We highlight how the modulation of the amount of oleic acid (OlAc) in the synthesis mixture influences the final composition of the M domain, the morphology of the MOx domain and, consequently, the magnetic properties of the hetero-structures. In the presence of high amounts of OlAc, a crystalline, magnetite MOx is mainly formed, coupled with a partial dealloying between Au and Cu in the M domain. Decreasing the amount of OlAc preserved the AuCu alloy and resulted in the formation of core–shell structures in the MOx. Here, a disordered, poorly crystalline, glass-like maghemite shell was coupled with a highly disordered iron rich core. An investigation into the magnetic properties revealed that the disordered phase was likely responsible for the observed exchange bias, rather than the interfacial stress between the M and MOx.